Component‐resolved analysis of IgA, IgE, and IgG4 during egg OIT identifies markers associated with sustained unresponsiveness. Issue 11 (13th June 2016) - Wright, B. L.; Kulis, M.; Orgel, K. A.; Burks, A. W.; Dawson, P.; Henning, A. K.; Jones, S. M.; Wood, R. A.; Sicherer, S. H.; Lindblad, R. W.; Stablein, D.; Leung, D. Y. M.; et al.
Abstract: Background: In a previously reported CoFAR study, 55 subjects with egg allergy underwent randomized, placebo‐controlled egg oral immunotherapy (eOIT). Active treatment induced desensitization in most and sustained unresponsiveness (SU) in a smaller subset. We hypothesized that component‐resolved analysis of IgE, IgG4, IgA, IgA1, and IgA2 may identify potential biomarkers of SU in OIT subjects. Methods: Longitudinal samples for 51 egg‐allergic subjects (37 active and 14 placebo) were available. Egg white (EW)‐, ovalbumin (OVA)‐, and ovomucoid (OVM)‐specific levels of IgA, IgA1, and IgA2 were quantified by ELISA. IgE and IgG4 to these antigens were quantified using ImmunoCAP ® . Clinical responders achieved SU to egg; all others were considered nonresponders. Between‐group comparisons were made among active and placebo, as well as responders and nonresponders. Results: No placebo subjects achieved responder status. Through month 48, among the 37 active subjects, baseline IgE‐OVM was lower in responders (median 3.97 kU/l, n = 19) than in nonresponders (10.9 kU/l, n = 18, P = 0.010). Logistic regression analysis revealed that lower baseline IgE‐EW ( P = 0.038), IgE‐OVM ( P = 0.032), and a higher IgG4/IgE‐OVM ratio ( P = 0.013) were associated with clinical response. Relative increases in IgG4‐EW, IgA‐EW, and IgA2‐EW were observed in responders ( P = 0.024, 0.024, and 0.029, respectively). IgG4/IgE, IgA/IgE, and IgA2/IgE ratios for EW and IgA/IgE ratio for OVA were found to be significantly elevated among responders ( P = 0.004, 0.009, 0.028, and 0.008, respectively). Conclusions: Increased IgG4‐EW, IgA‐EW, and IgA2‐EW during eOIT are associated with clinical response to eOIT. Lower pretreatment IgE‐EW and IgE‐OVM are also associated with SU. Future studies are needed to evaluate and validate these potential biomarkers.